Construction and Key Technology of Coal Geology Cloud Based on Openstack. Issue 2 (October 2020) - Miao, Lintian; Duan, Zhonghui; Lv, Tingting; Zhang, Jianjun; Yang, Yang
Abstract: In order to promote the information and digital construction of coal geological work, promote the rapid development of green coal mines and smart coal mines. In this study, we developed the Coal Geology Cloud (CGC) using key technologies such as elastic computing, mass storage of map data, and cloud message queues. The research and development process is based on the secondary development of Openstack and mature cloud computing platform technology. The researchers adopted the four-layer technical architecture of Iaas, PaaS, SaaS and Client. At the same time, it combines coal mine GIS series software and cloud computing IaaS platform to form an object-oriented Coal Geology Cloud GIS solution. CGC realizes the collection, aggregation, storage, analysis, processing and display of coal geology and related information, and provides convenient online cloud services for the exploration, development, research and management of coal resources.